(3GdTeSjIs - (3GdcGJHj GdbRhjfj, fLe GdOjf, OHjQGf, Ydj Hf YeQ Hf Ydj, (B675 (3g`s
(3ChdgG (B:s
(3Cbhd gPg GdQSGdI eQJHI Ydi ebOeI hKdGK ebGdGJ hNGJeI CeG GdebOeI aaj eGgjI GdefWb hHjGf GdMGLI Edjg(B...s
(3BNQgG (B:s
(3Cf jchf LRA GdTjA eWdhHG HGdHQgGf dCf GdCLRGA GdKHhJ GdTjA(B. (3hdjcf gPG BNQ(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B4(3, U(B315s
(3GdCYdGe(B: (3L(B4(3, U(B315s
(3cTa GdXfhf(B: (3L(B2(3, U(B1063s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdadSaI hGdefWbs